Developing an Accessible Survey Completion Tool for People with Disabilities - Modesto, Cristiana; Pereira, Letícia Seixas; Duarte, Carlos (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2025)
Introduction: Surveys are a key method for collecting data, used in contexts ranging from national censuses to customer satisfaction assessments. Despite their clear utility, recent literature highlights their inaccessibility to people with disabilities. Objective: This paper outlines the development of a survey completion tool accessible to people with disabilities. Methodology: Key steps included identifying requirements for designing an accessible survey completion tool, implementing them, testing the tool with people with disabilities, and refning it based on identifed issues and suggested changes. Results: Overall, the tool was found to be accessible to people with diverse disabilities.